Assessment of Ovarian Reserve in Patients with Migraine - Aykal, Güzin; Uzun, Nurgül; Derbent, Aysel Uysal; Yeğin, Ayşenur (Headache Medicine, 2022)
Objective The aim of our study is to investigate the relationship between migraine and ovarian reserve. Methods The study group consists of women between the ages of 25-51, including 44 patients diagnosed with migraine and 43 controls. Ovarian reserves were performed by antral follicle count and measured anti-Müllerian hormone level. The cohort was divided into four subgroups according to age as follows: 30 years and below, 31-35 years, 36-40 years, and 41 years of age and above. Results Of the 87 individuals included in this study, 44 were migraine patients, and 43 were healthy controls. The mean ages of the study and control groups were 34.3 (minimum: 25, maximum: 51) and 36.5 (minimum: 27, maximum: 51) years, respectively. There was no statistically significant difference between the two groups regarding age (p=0.48). In the study and control groups, respectively; mean AMH levels were 2.67 ± 2.46 ng/mL and 2.55 ± 2.38 ng/mL (p=0.819), mean basal FSH levels were 7.92 ± 2.52 U/L and 9.11 ± 3.19 U/L (p=0.066), mean basal LH levels were 6.35 ± 3.59 U/L and 6.06 ± 2.86U/L (p=0.681), mean basal estradiol levels were 65.02 ± 69.54 ng/L and 49.47 ± 27.08 ng/L (p=0.244), and mean AFC were 10.9 ± 3.9 and 10.2 ± 3.7 (p=0.435). Between subgroups aged ≤30 years, serum anti-Müllerian hormone levels were found to be significantly different (p=0.036). There was no statistically significant difference between any age subgroups in terms of antral follicle count. Conclusion In conclusion, detecting possible reduction of ovarian reserves in reproductive-age (especially younger than 30 years) migraine patients by utilizing anti-Müllerian hormone and ultrasonographic markers would allow these women to make cognizant decisions regarding marriage and family planning, as well as inform them whether they are in early menopause risk